Dialogue at IPS (Policy Perspectives, 2023)
International Relations, Pakistan Affairs, Faith, Society & Law, Science & Technology, and Leadership & Governance are the core themes of the Institute of Policy Studies (IPS), Islamabad, which remained the focus of deliberations held at IPS during the past few months. The following write-up summarizes these discussions under the aforementioned themes.